Community satisfaction index on the quality of academic and non-academic services at Jambi University - Junaidi, Junaidi; Amir, Amri; Syaparuddin, Syaparuddin (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study aims to measure the community satisfaction index regarding the academic and non-academic services provided by Jambi University. The data used are sourced from community surveys involving students, alumni, faculty members, and administrative staff who receive services at Jambi University (faculties, institutes, units). The analytical tool used is descriptive statistical analysis. The analysis results show that the community satisfaction index for the quality of services at Jambi University is 76.09, falling within the service quality interval